FAKTOR MANAJEMEN SUMBER DAYA MANUSIA DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN PERGURUAN TINGGI - Abd. Aziz Hsb. (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2023)
This study aims to analyze the factors of human resource management to improve the quality of education in tertiary institutions, human resource management is analyzed in the dimensions of forming human resource management consisting of knowledge, skills, and personality of lecturers which are associated with the quality of education in tertiary institutions, the research was conducted on students at the Al-Barokah Islamic High School. The study was analyzed using descriptive and inferential analysis, from the results of the study for human resource management factors, namely the knowledge, skills, and personality of lecturers that have a positive and significant influence on improving the quality of education, the highest factor can be seen from the knowledge of lecturers and followed by other factors, namely knowledge of lecturers has an influence of 53.2%, the personality of the lecturer is 24.4%, and the skills of the lecturer are 10.4%. From the results of the study, it was concluded that improving the quality of education in tertiary institutions can be carried out with good human resource management, by identifying dimensions or forming factors that can provide a positive and significant role or influence, it is hoped that this will be able to provide real changes in efforts improving the quality of education in terms of managing human resources in tertiary institutions. For this reason, universities need the right strategy in providing changes to the quality of human resources so that they will be able to improve the quality of the learning process which will ultimately be able to improve the quality of education